Oral and skin microbiome as potential tools in forensic field. (December 2022) - Lovisolo, Flavia; Ogbanga, Nengi; Sguazzi, Giulia; Renò, Filippo; Migliario, Mario; Nelson, Andrew; Procopio, Noemi; Gino, Sarah
Abstract: The interest in the analysis of the human microbiome for personal identification purposes is based on the microbial diversity amongst individuals. The oral cavity hosts one of the most diverse and abundant microbial communities in the human body; the skin instead is a complex living ecosystem with unique microbial niches at different sites. Both skin and oral microbiomes are highly individual and relatively stable over time. As saliva and skin debris are often found at crime scenes, the analysis of their microbiome may represent a potential tool for personal identification. However, there are some gaps in knowledge on how factors such as age, sex, geographic origin, diet and pathologies can affect the composition of the microbiome. The aim of this study is to improve the existing knowledge by examining oral and skin microbiomes from the same individuals and evaluating the variability between anatomical sites and donors. For this study, 50 individuals living in Italy donated oral swab samples and provided information regarding their diet, lifestyle, health status, antibiotic use, and other demographic data. Skin swabs from 11 of the 50 individuals were also analysed and compared to the oral swabs from the same donors. All analyses were done through metabarcoding of the 16S rRNA region of DNA extracted from the samples. This research outlines the potential use of oral and skin microbiome signatures as added evidence in personal identification, providing useful investigative clues for future forensic caseworks.